The case of consonantal harmony in Bakairi Language (Carib) - Souza, Tania Conceição C. de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The aim of this paper is to focus on Bakairi’s consonant harmony case in the light of autosegmental theory. It is our intention to verify if the strategies offered by the autosegmental account for the facts listed in Bakairi. It will also be discussed the real need to postulate a phonemic level for Bakairi: it is the phenomenon of harmony that conditions the deaf / sonic features of the occlusives and fricatives in the bulge of words. Thus, the phonemic contrast seems to disappear. Finally, it will be shown how consonant harmony developed in the language.